2013
DOI: 10.5120/10172-4897
|View full text |Cite
|
Sign up to set email alerts
|

Plant Recognition from Leaf Image through Artificial Neural Network

Abstract: Getting to know the details of plants growing around us is of great importance medicinally and economically. Conventionally, plants are categorized mainly by taxonomists through investigation of various parts of the plant. However, most of the plants can be classified based on the leaf shape and associated features. This article describes how Artificial Neural Network is used to identify plant by inputting leaf image. Compared to earlier approaches, new input features and image processing approach that matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…The results of these methods are then combined with the help of incremental classification algorithm which provides 81.1%accuracy. The research document introduced by Shayan Hati, et al, [7] includes an article that describes how Artificial Neural Network is used to identify plant by inputting leaf image. Compared to earlier approaches, new input features and image processing approach that matter in efficient classification in Artificial Neural Network have been introduced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of these methods are then combined with the help of incremental classification algorithm which provides 81.1%accuracy. The research document introduced by Shayan Hati, et al, [7] includes an article that describes how Artificial Neural Network is used to identify plant by inputting leaf image. Compared to earlier approaches, new input features and image processing approach that matter in efficient classification in Artificial Neural Network have been introduced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hati and Sajeevan [ 13 ] calculated the angle of apex and base angle in and . Ab Jabal et al [ 14 ], and Arun Priya, Balasaravanan and Thanamani [ 15 ] only found the angle of leaf tip in from leaf length regardless of its base information.…”
Section: Related Workmentioning
confidence: 99%
“…Previous researchers, such as Hati and Sajeevan [ 13 ], Arun Priya [ 15 ], measured the angle of the leaf apex and base to make this measurement as a parameter to interpret the leaf apex. However, in the perspective of botanical knowledge, all leaf bases with the same angle are actually not the same.…”
Section: Related Workmentioning
confidence: 99%
“…It can make simple judgments by simulating the human brain, so it has been widely used in plant disease detection and recognition. Hati et al [14] programmed it with 400 leaves from 20 plants and tested 134 leaves, achieving an accuracy of 92%.…”
Section: Introductionmentioning
confidence: 99%